Early Childhood Role Models and Gross Motor Activities Could Assist to Build a Sense of Enterprise in Kids - Guruh Herman Was’an; Molbi Febrio Harsanto; Suratminingsih Suratminingsih; HM Usman (Pasundan Community Service Development, 2023)
This study explores the impact of gross motor activities and role-play centers on cultivating entrepreneurial spirit in early childhood. Employing both qualitative and quantitative methods, the research involved 50 children aged 4-6 years from various kindergartens. Gross motor activities such as running and jumping were integrated with role-playing games that included simulations of small business activities. The study found that a combination of physical activities and social role-playing significantly enhanced the children’s cognitive, social, and emotional skills, which are crucial components of an entrepreneurial mindset. Results showed improvements in self-confidence, creativity, and collaborative abilities in children, in addition to strengthening their understanding of basic business and economic concepts. These findings highlight the importance of incorporating entrepreneurial education in early childhood curriculums, laying the foundation for the development of entrepreneurial skills and attitudes for the future.